Counselling-based psychosocial intervention to improve the mental health of abused pregnant women: a protocol for randomised controlled feasibility trial in a tertiary hospital in eastern Nepal. Issue 4 (23rd April 2019) - Sapkota, Diksha; Baird, Kathleen; Saito, Amornrat; Rijal, Pappu; Pokharel, Rita; Anderson, Debra
Abstract : Introduction: The strong correlation between domestic and family violence (DFV) and mental health has been well documented in studies. Pregnancy is a period when both DFV and mental distress tend to occur and/or accentuate. Although limited, available evidence from developed countries has shown continual support and education as psychological first aid that can reduce DFV and improve mental health. However, there is significantly less number of studies from resource-constrained countries; thus, there continues to be a substantial gap in knowledge and awareness regarding effective interventions for DFV. Methods and analysis: A two-arm randomised trial with a nested qualitative study has been planned to assess feasibility and treatment effect estimates of a counselling-based psychosocial intervention among pregnant women with a history of abuse. A total of 140 pregnant women who meet the inclusion criteria will be recruited into the study. Block randomisation will be used to allocate women equally into two groups. The intervention group will receive a counselling session, an information booklet and continuous support by a researcher, while women in the control group will receive contact information of local support services. Feasibility measures, such as rates of recruitment, consent and retention, will be calculated. Qualitative interviews with participants and healthcare providers will explore the acceptability and usability of the intervention. Outcome measures, such as psychological distress, quality of life, social support and self-efficacy, will be measured at baseline, 4 weeks postintervention and 6 weeks postpartum. Ethics and dissemination: This study has obtained ethical approval from the Griffith University Human Research Ethics Committee, the Nepal Health Research Council and the Institutional Review Board of a tertiary hospital in Dharan, Nepal. The findings will be disseminated via peer-reviewed publications and conference presentations and will be used to inform a future multicentre trial. Trial registration number: 12618000307202; Pre-results.